(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2016)
Focusing on Soviet architectural and urban production in the 1920s and 1930s, this article investigate and questions the notion of Sotsgorod (Socialist town). It presents also the principal aspects of the General plan for reconstruction of Moscow of 1935. Rather than stressing discontinuity, as is usually the case, it underscores underlying continuity in terms of ideas and personalities, and presents an in-depth view of the architectural and urban fabric of the Stalinist period. Juxtaposing contemporary declarations with published and archival material, as well as observations of realized projects, it higlights the shared responsability of politicians and architects. Based chiefly on the declarations of one of the countryâ€™s most powerfull decision-makers, the politician Lazar Kaganovih, who dealt extensively with the architectural profession, it demonstrates how urbanism was not simply â€œimposed from aboveâ€, contending instead that the new architectural paradigms of the 1930s emerged in equal measure from the aesthetics of the political cadre, input from the architectural community, and the necessity of taking into consideration the prevaling economic conditions.